Communication Strategy of Village Head's in Distributing Direct Village Fund Cash Assistance to Poor Communities Affected by Covid-19 in Teluk Mengkudu District - Umi Salamah; Mailin Mailin; Elfi Yanti Ritonga (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aim of this study is to find out communication strategy of village head's in distributing direct village fund cash assistance to poor communities. This research uses a qualitative approach, as a form of effort to provide answers to the problems that have been described. The result of this study show that StrategyCommunication is planning in delivering messages through a combination of various elements of communication such as frequency, formality, content and communication channels so that the messages conveyed are easily accepted and understood and can change attitudes or behavior in accordance with the purpose of communication.Strategycommunication is a blend and planning communication (communication planning) and communication management (communication management) to achieve a goal. To achieve this goal, the communication strategy must be able to show how its tactical operations must be carried out in the sense that the approach (approach) can be different at any time depending on the situation and conditions. Communication strategies are closely related and related between the goals to be achieved with the consequences (problems) that must be taken into account, then plan how to achieve the consequences in accordance with the expected results or in other words the goals to be achieved.